2022
DOI: 10.1038/s41598-022-05962-w
|View full text |Cite
|
Sign up to set email alerts
|

Conservation agriculture based integrated crop management sustains productivity and economic profitability along with soil properties of the maize-wheat rotation

Abstract: Field experiments were conducted to evaluate eight different integrated crop management (ICM) modules for 5 years in a maize-wheat rotation (MWR); wherein, ICM1&2-ˈbusiness-as-usualˈ (conventional flatbed maize and wheat, ICM3&4-conventional raised bed (CTRB) maize and wheat without residues, ICM5&6-conservation agriculture (CA)-based zero-till (ZT) flatbed maize and wheat with the residues, and ICM7&8- CA-based ZT raised bed maize and wheat with the residues. Results indicated that the ICM7&am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…The sustainable yield index (SYI) [ 65 , 66 ] and coefficient of variation (CV) [ 67 ] were used to evaluate yield sustainability and yield stability. The higher the SYI value, the better the yield sustainability; the lower the CV value, the better the yield stability: in which is the average yield (kg hm −2 ), σ is the standard deviation (kg hm −2 ), and Y max is the highest yield (kg hm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sustainable yield index (SYI) [ 65 , 66 ] and coefficient of variation (CV) [ 67 ] were used to evaluate yield sustainability and yield stability. The higher the SYI value, the better the yield sustainability; the lower the CV value, the better the yield stability: in which is the average yield (kg hm −2 ), σ is the standard deviation (kg hm −2 ), and Y max is the highest yield (kg hm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…CA aims to maximize agricultural yields and farm incomes while minimizing the negative environmental effects of traditional agriculture ( Parihar et al, 2016 ). Zero-tillage is essential nowadays due to reduction in the cost of cultivation, greater retention of soil moisture, decreased energy consumption, increased farm revenues, improved soil biophysical and chemical characteristics, carbon sequestration, fewer greenhouse gas emissions, and comprehensive natural resource conservation ( Paul et al, 2014 ; Jakhar et al, 2018 ; Varatharajan et al, 2019b ; Pooniya et al, 2022 ). MWCS is India’s 3rd largest cropping system, covering ∼1.8 million ha and accounting for 3% of the country’s total food production ( Pooniya et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, each of these crops requires effective fertilizer management strategies in order to reach their full yield potential. The MWCS is recently being followed in the Indo-Gangetic plains region (IGPR), which is already facing numerous challenges, such as natural resource degradation, declining agricultural productivity, and environmental concerns ( Paul et al, 2014 ; Pooniya et al, 2017 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…(salinisation/alkalisation), low resource-use efficiencies, water table decline and higher associated cost and energy in water extraction (Kumar et al, 2021(Kumar et al, , 2022Harish et al, 2022), besides substantial weed management costs and the emergence of weed resistance (Dass et al, 2017;Choudhary et al, 2021), severe incidence of pests, diseases and minor pest resurgence, climatic vulnerabilities like heat/cold waves, terminal drought stress and other numerous production vulnerabilities that collectively threaten the sustainability of RWCS in IGPR (Paul et al, 2014;Bhatt et al, 2016;Pooniya et al, 2018Pooniya et al, , 2022. To overcome these vulnerabilities, one strategy could be to replace rice with maize, legumes and other underutilised crops that require less water and other resources (Choudhary et al, , 2020Harish et al, 2021Harish et al, , 2022Singh et al, 2021Singh et al, , 2022aPooniya et al, 2022); and hence, diversify the system for better productivity, profitability and resource use.…”
Section: Introductionmentioning
confidence: 99%
“…The application of ICM techniques helps in raising RUE and system productivity (Choudhary et al, 2020). Earlier reports in major cropping systems of India like RWCS, maize-wheat cropping system (MWCS), soybean-wheat under ICM indicated that CA-based treatments recorded higher crop yields due to improved crop physiological and photosynthetic characteristics, modulation of microclimate and resilience to environmental stresses, enhanced soil fertility and favourable soil microbiome (Choudhary et al, , 2020Varatharajan et al, 2019a;Singh et al, 2020Singh et al, , 2021Singh et al, , 2022aBiswakarma et al, 2021;Pooniya et al, 2022). Our extensive literature review revealed that the majority of earlier studies focused on individual components of crop management, i.e., crop establishment, tillage, nutrient, weed, water, energy management, etc.…”
Section: Introductionmentioning
confidence: 99%